EFFECT OF FINANCIAL INTEGRATION ON THE PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES IN ABUJA, NIGERIA - Ibrahim, Muhammed (African Journal of Social and Behavioural Sciences, 2025)
This study examined the effect of Financial Integration on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Abuja, Nigeria, with a focus on credit accessibility and insurance coverage as key dimensions of Financial Integration. The main objective was to assess how access to financial services influences the growth and sustainability of MSMEs in the region. The research adopted a quantitative approach, utilising a survey design to collect data from a population of 2,825 MSMEs. The sample size was determined using the Krejcie and Morgan (1970) formula, resulting in a sample of 373 MSMEs, which were selected through a stratified random sampling technique to ensure representation across various sectors and locations. Data were collected using structured questionnaires and analysed using descriptive statistics, Pearson correlation, and multiple regression analysis. The findings revealed that both credit accessibility and insurance coverage had significant positive impacts on MSME performance, with insurance coverage showing a marginally stronger influence. The study concluded that Financial Integration plays a critical role in enhancing the performance of MSMEs in Abuja, Nigeria. Recommendations include expanding access to credit and insurance services, implementing financial literacy programs, and improving financial infrastructure to support the growth and sustainability of MSMEs in the region. These measures are essential for fostering economic development and reducing poverty in Abuja, Nigeria.